Oil and public opinion in the Middle East. - Hirst, David (London : Faber, 1966)
There are few issues of international concern which are more bedeviled by preconceptions and emotional bias than Middle East oil. The book looks at the public opinion on oil in the Middle East.
Includes bibliographical footnotes and index.
ii 18/01/2019
Loans
Keywords: Petroleum industry and trade; Middle East